Regulatory Model for Taxation of Non-Fungible Token Digital Assets as Creative Works in Indonesia - Hidayah, Khoirul; Esha, Muhammad In'am; Firdaus, Dwi Hidayatul; Ramadhita, Ramadhita (Jambura Law Review, 2025)
The Non-Fungible Token (NFT) is one form of trade utilising crypto assets as a medium of exchange. This system has proven effective in assisting creators in protecting both their economic and moral rights. However, the existence of Regulation of the Minister of Finance No. 68/PMK.03/2022 concerning Value Added Tax and Income Tax on Cryptocurrency Trading does not adequately address the phenomenon of NFT trading. This raises an intriguing issue regarding the formulation of tax collection for NFTs as digital assets that can be traded and serve as a source of state revenue. This study employs  a socio-legal approach with qualitative methods. Based on an analysis of legislation, the theory of justice, and tax collection theory, three alternative models for regulating income tax and VAT on NFTs in Indonesia are proposed. The first model suggests specific regulation in the form of a Minister of Finance Regulation. The second model recommends classifying NFT trading platforms as Permanent Establishments (PE). The third model advocates for the application of tax treaties to prevent double taxation. This study is expected to contribute to the development of NFT taxation regulations in Indonesia.